1985
DOI: 10.1115/1.3185973
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Model of Cutting Dynamics. Part 2: Verification

Abstract: The dynamic force model developed in the preceding paper [1] is further examined. The analysis shows a successful prediction of the forms of stability boundary over a wide range of cutting speed. It reveals that the cutting force acting on tool rake face controls the high-speed stability, while the ploughing force acting on tool nose region dominates the low-speed stability. A series of cutting tests were carried out to examine the validity of the model. The result shows a fairly good agreement between the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Early two-dimensional modeling by Tlusty and Ismail [ 191 found that the tool can lose contact with the workpiece at large chatter amplitude, thus improving chatter stability for turning and milling. The nonlinear delayed differential equation (DDE) model of Wu and Liu [25] included fluctuations in the mean friction coefficient due to chip removal, and yielded results that are consistent with experimental chatter dynamics [26]. Berger et al [2] used the model of Ref.…”
Section: Introductionmentioning
confidence: 81%
“…Early two-dimensional modeling by Tlusty and Ismail [ 191 found that the tool can lose contact with the workpiece at large chatter amplitude, thus improving chatter stability for turning and milling. The nonlinear delayed differential equation (DDE) model of Wu and Liu [25] included fluctuations in the mean friction coefficient due to chip removal, and yielded results that are consistent with experimental chatter dynamics [26]. Berger et al [2] used the model of Ref.…”
Section: Introductionmentioning
confidence: 81%
“…The subsequent studies show the importance of regenerative effects [3][4][5][6], and structural dynamics [7][8][9]. Finally, the role of the dry friction and the stick-and-slip motion [10][11][12] was indicated and studied extensively. Recently, apart from the widely studied conditions of regular chatter vibrations, noise like chaotic oscillations caused by various system nonlinearities were predicted and detected [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The following studies showed the importance of time-delayed regenerative effects [8,9,10,11] and structural dynamics [12,13,14]. It was later demonstrated that dry friction and stick-and-slip motion may be essential factors leading to chatter vibrations [15,16,17]. Recently, chaotic and intermittent oscillations caused by various system nonlinearities were theoretically predicted and experimentally detected [18,19,20,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%